PEMBINAAN KARAKTER ANAK SEKOLAH MINGGU BERBASIS KASIH, DISIPLIN, DAN TANGGUNG JAWAB - Butarbutar, Imelda; Hutahaean, Sihol Giot Marito; Aritonang, Ronauli; Lubis, Salti Lusmita; Sinaga, Santun (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
Character formation in children is an essential component of church ministry through Sunday School activities as a means of nurturing faith, morality, and behavior from an early age. This community service program aims to describe and analyze the effectiveness of Bible storytelling in shaping the character of Sunday School children at HKBP Tapian Nauli Ressort Lumban Lobu District IV Toba. The program employed a descriptive qualitative approach with a participatory method through the implementation of creative and interactive Bible storytelling activities. Data were collected through observation, documentation, and activity reflection during three learning sessions. The results indicate that Bible storytelling improved children’s understanding of biblical moral messages while fostering positive character traits such as obedience, courage, love, cooperation, and respect for parents. In addition, the use of visual media, teaching aids, and educational games significantly increased children’s learning interest and active participation throughout the activities. These findings affirm that participatory, contextual, and creative Bible storytelling serves as an effective pedagogical strategy in supporting Christian value-based character formation among children. Therefore, this method can be utilized as an alternative Sunday School instructional model to promote children’s moral and spiritual development sustainably.